2014
DOI: 10.1371/journal.pone.0109240
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Depressive Reaction among Resident Survivors after the Tsunami following the Great East Japan Earthquake, March 11, 2011

Abstract: ObjectivesThe Great East Japan Earthquake caused a gigantic tsunami which devastated coastal areas of northern Japan on 11 March 2011. Despite the large number of ‘resident survivors’ who continued to reside in their damaged houses on the second or upper floors, research on the mental health of these individuals has been limited. This study explored the prevalence of depressive reaction and risk factors for depressive reaction among these resident survivors.MethodsA cross-sectional household health support nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…The present study revealed the highest OR for insomnia in middle-aged participants (50s), which differs from that reported by previous studies, which showed that the highest prevalence of insomnia was in elderly people, majorly cause by aging. Although specific reasons for the highest prevalence of insomnia in the middle-aged group were not determined in this study, previous studies indicated that the psychological stress and depressive reactions among the disaster victims after GEJE was distinctly observed in the middle-aged group (Koyama et al 2014;Matsubara et al 2014). Evident from the delayed increase of suicide rates in middle-aged GEJE victims in the disaster-affected areas (Orui et al 2015), continuous and intensive healthcare services are worth considering in support of these people.…”
Section: Discussionmentioning
confidence: 74%
“…The present study revealed the highest OR for insomnia in middle-aged participants (50s), which differs from that reported by previous studies, which showed that the highest prevalence of insomnia was in elderly people, majorly cause by aging. Although specific reasons for the highest prevalence of insomnia in the middle-aged group were not determined in this study, previous studies indicated that the psychological stress and depressive reactions among the disaster victims after GEJE was distinctly observed in the middle-aged group (Koyama et al 2014;Matsubara et al 2014). Evident from the delayed increase of suicide rates in middle-aged GEJE victims in the disaster-affected areas (Orui et al 2015), continuous and intensive healthcare services are worth considering in support of these people.…”
Section: Discussionmentioning
confidence: 74%
“…The country has been repeatedly affected by various types of major natural disasters, including typhoons, flooding, landslides, earthquakes, and volcano eruptions. Part of the population has thus experienced natural disasters, and mental health has been a major topic in post-disaster studies (Matsubara et al 2014;Nakamura et al 2014;Hikichi et al 2016;Tsuchiya et al 2017). The aim of the present study was to assess whether the effects of social capital on mental health could differ between those who had previously experienced disasters and those who had not.…”
Section: Introductionmentioning
confidence: 97%
“…Cognitive social capital is consistently suggested to exert protective effect on post-disaster mental health (Hikichi et al 2016;Tsuchiya et al 2017). However, the findings for structural social capital are rather inconsistent: while this component is protective in some settings (Matsubara et al 2014;Nakamura et al 2014), it may impair mental health in other settings (Wind et al 2011). Several hypotheses for this phenomenon have been proposed, such as contagion of effect and inverse relationships (Wind et al 2011;Noel et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1 The experience of disaster presents a significant burden on the mental health of survivors. [2][3][4] Depression in older adults is strongly associated with being house-bound, 5 which may lead to a decline in physical and cognitive function and eventually to premature death. 6 To clarify the factors that contribute to mental health recovery after a disaster, several postdisaster surveys have been previously conducted.…”
Section: Introductionmentioning
confidence: 99%